An Overview of the Courts Catalyzing Change Preliminary Protective Hearing Benchcard Study. (15th May 2013) - Russell, Jesse; Summers, Alicia
Abstract This paper presents an overview of the Courts Catalyzing Change: Achieving Equity and Fairness in Foster Care Preliminary Protective Hearing Benchcard Study. In the fall of 2009, the National Council of Juvenile and Family Court Judges (NCJFCJ) began a study to examine the effects associated with judges' use of the Preliminary Protective Hearing Benchcard. For this study, data were gathered from case file information (both court and agency files) and from courtroom observations of more than 500 children in Los Angeles, California; Omaha, Nebraska; and Portland, Oregon. Data from a baseline sample were collected at each of the three sites, and judicial officers at each site were randomly assigned to either a Benchcard group or a control group. Benchcard implementation appears to be associated with more discussion and higher quality discussion of key dependency topics during preliminary protective hearings. Benchcard implementation also corresponds to increased judicial inquiry and parental engagement. Benchcard use also was associated with more family placements—placement with a charged parent, a non‐charged parent, or a relative—at the initial hearing and even more family placement at adjudication when comparing the same judges before and after Benchcard implementation. Similarly, the percentage of children who were reunified with the charged parent at the initial hearing and the adjudication hearing increased after Benchcard implementation.